The socially networked classroom teaching in the new media age - Kist, William (Thousand Oaks, Calif. Corwin, 2010)
"This book demonstrates how pioneering teachers have successfully integrated screen-based literacies into their instruction."--Cover.
The writing is on the screen : social networking is here to stay -- Short : social networking in a low-tech environment -- Tall : social networking in a medium-tech environment -- Grande : social networking in an unlimited tech environment -- Venti : social networking in an unlimited tech environment -- Refill : continuing the dialogue.
Keywords: Internet in education; Online social networks